2021
DOI: 10.1101/2021.06.14.448338
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Here be dragons: important spatial uncertainty driven by climate data in forecasted distribution of an endangered insular reptile

Abstract: The effect of future climate change is poorly documented in the tropics, especially in mountainous areas. Yet, species living in these environments are predicted to be strongly affected. Newly available high-resolution environmental data and statistical methods enable the development of forecasting models. Nevertheless, the uncertainty related to climate models can be strong, which can lead to ineffective conservation actions. Predicted studies aimed at providing conservation guidelines often account for a ran… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 69 publications
(88 reference statements)
0
9
0
Order By: Relevance
“…We identified local differences between predicted invasion risks using different climate data sources. Differences may be driven by the selection of different variables (e.g., models calibrated with CHELSA data selected ‘Daily temperature range’ but not with Worldclim for P. grandis ); however, a recent study showed that differences can persist even when the same predictors are selected (Dubos et al 2022a; see also Jiménez-Valverde et al 2021). The mismatch may be better explained by the methods used to compute the climatologies.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We identified local differences between predicted invasion risks using different climate data sources. Differences may be driven by the selection of different variables (e.g., models calibrated with CHELSA data selected ‘Daily temperature range’ but not with Worldclim for P. grandis ); however, a recent study showed that differences can persist even when the same predictors are selected (Dubos et al 2022a; see also Jiménez-Valverde et al 2021). The mismatch may be better explained by the methods used to compute the climatologies.…”
Section: Discussionmentioning
confidence: 99%
“…Since we had no a priori on which climate data source is best for ecological modelling, we based the ranking on the mean value between predictions obtained between CHELSA and Worldclim. To account for uncertainty, we penalised the mean prediction by subtracting its standard deviation (mean – SD), following the approach developed by Kujala et al (2013) applied to single species (Dubos et al 2022a). This enabled us to prioritise areas where the invasion risk is most-consistently identified as high across climate data sources and model replicates.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations